Double-Blind, Placebo-Controlled Trial of Cyproterone Acetate to Prevent Flare-Up Effect on Dogs Implanted With Deslorelin - Masson, Sylvia; Medam, Tiphaine; Raibon, Elsa; Fontaine, Christelle; Levy, Xavier (Frontiers in Veterinary Science, 2021)
Deslorelin slow-released implants are registered in Europe for the reversible suppression of fertility in male dogs. After administration, a time-limited increase in sex hormones concentration and related behavioral problems may be observed. The aim of this work was to assess whether cyproterone acetate, a synthetic progestogen, can prevent this flare-up effect. Eighteen privately-owned entire male dogs were enrolled in this double-blind, placebo-controlled, randomized clinical trial. All subjects received a 4.7 mg deslorelin implant by SC route and 1-3 capsules containing either cyproterone acetate 2 mg/kg (N=9) or a placebo (N=9), by oral route BID for 14 days, depending on the dog’s weight. The dogs were followed for 28 days. An increase in the blood testosterone concentration was observed in respectively 9/9 and 7/9 dogs of the control and cyproterone groups (p = 0.47). However, a worsening of the sex hormone related problems (i.e., urinary marking, mounting, aggressiveness towards other dogs and/or escape) was only observed in the placebo group, in 56% or 66% of the dogs as measured by respectively the veterinarian and the owners. Our study suggests that cyproterone acetate is effective and safe to supress the deslorelin induced behavioural flare-up effect, but not the rise in testosterone.